Make a Match and Student Engagement in Akidah Akhlak: A Quasi-Experimental Study at an Islamic Junior Secondary School - Warastri, Niken Diah; Nasrin, Samima; Octafiona, Era (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
Student engagement remains a persistent concern in Akidah Akhlak instruction, particularly when classroom activity is dominated by teacher-centred explanation. This study examined whether the Make a Match cooperative learning method was associated with higher engagement among eighth-grade students at an Indonesian Islamic junior secondary school, locally known as Madrasah Tsanawiyah (MTs), specifically MTs NU Pesisir Tengah. A quantitative quasi-experimental posttest-only control-group design involved 60 students from two intact classes (experimental n = 30; control n = 30). The experimental class received Make a Match instruction across three meetings, whereas the control class received conventional lecture-based instruction on the same topic. Engagement was measured with a 20-item five-point questionnaire operationalising attention, cooperation, and problem-solving. Shapiro-Wilk and Levene tests supported the use of an independent-samples t test. The experimental group reported a higher mean engagement score (78.17) than the control group (72.33), with a significant mean difference of 5.83, t(58) = 3.804, p < .001, 95% CI [2.76, 8.90], and Cohen's d = 0.98. The result indicates a substantial between-group difference; however, the absence of a pretest limits strong causal attribution. Make a Match may therefore be a useful participatory strategy for supporting engagement in Akidah Akhlak classrooms with similar characteristics.